Antibiotic Resistance Profile Of Uropathogenic Bacteria In A Tertiary Care Hospital, Chattogram, Bangladesh: A Focus On Multidrug-Resistant Strains - Faruq, Muhammad Omar; Newaz, Taslima; Newaz, Taslima; Alamder, Mezanoor Rashid; Rudra, Sandipawn; Faruq, Omar; Das, Anupam; Sarkar, Aka (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: In Bangladesh, Urinary Tract Infection (UTI) is the most common bacterial infection, and misuse of antibiotics is causing Antimicrobial Resistance (AMR) rapidly increasing. The purpose of this study is to identify the antibiotic resistance pattern of bacterial uropathogens in patients with multidrug resistance rates at a tertiary hospital in Chandanaish Upazilla, Chattogram. Materials and methods: An institution-based crosssectional study was done in the clinical laboratory for the diagnosis of patients attending BGC Trust Medical College and Hospital. The data of urine samples and their antibiotic sensitivity patterns were obtained from the laboratory register book. Secondary data were collected and entered into the SPSS version 22 computer software package for univariate and bivariate analysis. Results: Out of 891 registered patient data sets, 886 results were taken and investigated. About 27% (239) people had a urinary tract infection, and the maximum count of the isolates, 81.6% (195) were from females. The highest prevalence was obtained among the age groups of 19–30 years (36.8%). Escherichia coli was the most prevalent organism, 64.9% (155). All the isolatesshowed the maximum resistance to cefuroxime and cefradin, ranging from 85-100%. The antibiotic resistant rate and multi-drug resistant rate were 97.9% and 65.81%, respectively. E. coli showed the highest drug resistance and multi-drug resistance 65.9% and 64.3%. Conclusion: The study highlights a high prevalence of antibiotic resistance and multidrug resistance in bacterial uropathogens, notably Escherichia coli. Resistance to critical antibiotics like cefuroxime and cefradine underscores the need for enhanced antibiotic stewardship and control measures to combat Antimicrobial Resistance (AMR). JCMCTA 2025 ; 36 (2) : 92-98